Riesgo laboral y estrés laboral en enfermeros que atienden pacientes con COVID-19 en Emergencia del Instituto Nacional de Enfermedades Neoplásicas, 2020 - Romero-Esteban, Herberth-Clerk (2022)
The current COVID-19 pandemic is generating multiple changes in the country's health reality, including situations typical of the nursing professional practice and its environment. Objective: To determine the relationship between occupational risk and work stress in nurses who care for patients with COVID-19 in Emergency at the National Institute of Neoplastic Diseases (INEN). Methodology: The study had a quantitative, correlational, cross-sectional and non-experimental design approach. The population consisted of 58 nurses working in the INEN Emergency Service (Lima-Peru). Two instruments were used: "Questionnaire to measure occupational risk in nurses" and the "Scale for measuring work stress in nurses". Results: 46.6% of the participants presented a high occupational risk level, 43.1% medium risk and 10.3% low occupational risk. The biological risk and psychosocial risk showed a mainly high level (69.0% and 53.4% respectively) and the chemical risk (46.6%), physical (56.9%) and ergonomic (48.3%) a preponderant average level. On the other hand, the work stress present in the participants was 46.6% high level, 32.8% medium level and 10.3% low. Regarding the association of variables, a p = 0.005 (direct correlation) was obtained between occupational risk and occupational stress and a Spearman Rho coefficient of 0.364. On the other hand, values p = 0.029, p = 0.200, p = 0.007, p = 0.102, were obtained for biological risk, chemical risk, physical risk and ergonomic risk respectively, which determines the non-existence of association of these variables with the work stress; On the other hand, a value of p = 0.007 of the social risk (direct correlation) and a Spearman's Rho coefficient = 0.348 were presented. Conclusion: The occupational risk was significantly related to the work stress of the nurses who care for patients with COVID-19 in the INEN Emergency Department. Likewise, regarding the dimensions of occupational risk: psychosocial risk was also significantly related to occupational stress. On the other hand, biological risk, chemical risk, physical risk and ergonomic risk were not related to work stress.